Regulatory signaling pathways of osteoblast autophagy in periprosthetic osteolysis - Gu, YingChu; Wu, ZeRui; Xie, Heng; Fang, Tao; Wang, QiuFei; Gu, Ye (Frontiers in Cell Death, 2024)
Periprosthetic osteolysis is a difficult-to-treat complication of arthroplasty. The pathological mechanisms of periprosthetic osteolysis are mainly weakened function of osteoblasts and excessive activation of osteoclasts. Many studies have demonstrated that the imbalance between the formation of bone by osteoblasts and the absorption of bone by osteoclasts is the direct cause of osteolytic diseases. Autophagy, as an important self-protective cellular mechanism, has significant effects on the regulation of osteoblast function, such as osteoblast differentiation, proliferation, and apoptosis. Osteoblasts, which play an important role in maintaining bone homeostasis, have attracted increasing attention in recent years. Up till now, Several signaling pathways have been proved to regulate autophagy of osteoblasts, including the AMPK, NF-κB, FoxO3 and other signaling pathways. This article reviews the recent progress in understanding osteoblast autophagy and mitophagy in the context of periprosthetic osteolysis and the signaling pathways which are involved in these processes. By summarizing previous studies describing the mechanism underlying osteoblast autophagy, we wish to contribute new therapeutic ideas and potential therapeutic targets for periprosthetic osteolysis.